Journalism Standards of Work Today Using History to Create a New Code of Journalism Ethics. - Banning, Stephen A. (Cambridge Scholars Publisher, 2020)
This research examines journalism ethics to answer the questions of whether we still need journalism ethics in the twenty-first century, if it is possible to exercise journalistic standards of work and, if so, on what values should these ethics be based in a world much different from that which existed when the first journalism codes of ethics were formulated in the nineteenth and early twentieth centuries. To distil the motivations and essence of the early journalistic standards of work, the book discusses the function of media in a democracy and the formation of mass media during the first i.